Treatment of Premenstrual Breakthrough of Depression With Adjunctive Oral Contraceptive Pills Compared With Placebo. Issue 5 (October 2017) - Peters, Whitney; Freeman, Marlene P.; Kim, Semmie; Cohen, Lee S.; Joffe, Hadine
Abstract: Purpose/Background: Two-thirds of women with depressive disorders report reemergence of depression premenstrually, or premenstrual exacerbation (PME), despite effective treatment of the underlying mood disorder during the remainder of the cycle. There is a paucity of studies that rigorously assess treatments targeting PME. Open-label data suggest that augmentation of antidepressants with the oral contraceptive pill (OCP) drospirenone and ethinyl estradiol (DRSP/EE) improves depressive symptoms that break through treatment premenstrually. We now report results of a randomized placebo-controlled OCP augmentation trial. Methods: Women with unipolar depressive disorders in remission on stable antidepressant doses with a 30% increase in Montgomery-Åsberg Depression Rating Scale (MADRS) scores from the follicular to luteal phase were randomized to double-blind augmentation of antidepressant with either DRSP/EE or placebo for 2 months. The MADRS and Daily Record of Severity of Problems (DRSP) measures were anchored to the menstrual cycle phase. Findings/Results: Of 32 women randomized, 25 (n = 12 DRSP/EE, n = 13 placebo) completed the trial. Premenstrual MADRS scores declined by a median of 43.6% and 38.9% ( P = 0.59), and premenstrual DRSP scores declined by a median of 23.5% and 20.9% ( P = 0.62) in the DRSP/EE and placebo groups, respectively. There was a trend toward greater improvement in premenstrual DRSP scores for women with fewer lifetime depressive episodes ( r = −0.40, P = 0.06). Implications/Conclusions: Findings from this small randomized trial suggest that OCP augmentation of antidepressants may not be effective for treating premenstrual breakthrough of depression. Future studies should target women established to have hormonal sensitivity prior to antidepressant therapy and those with fewer lifetime depressive episodes.